2016
DOI: 10.1128/jvi.01293-16
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Studies Show that Sequence Variability Contributes to Marked Variation in Hepatitis B Virus Replication, Protein Expression, and Function Observed across Genotypes

Abstract: The hepatitis B virus (HBV) exists as 9 major genotypes (A to I), one minor strain (designated J) and multiple subtypes. Marked differences in HBV natural history, disease progression and treatment response are exhibited by many of these genotypes and subtypes. For example, HBV genotype C is associated with later hepatitis B e antigen (HBeAg) seroconversion and high rates of liver cancer compared to other HBV genotypes, whereas genotype A2 is rarely associated with HBeAg-negative disease or liver cancer. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
62
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 35 publications
7
62
1
Order By: Relevance
“…There may be several explanations for our findings. HBsAg generation is reflective not only of cccDNA transcriptional activity, but also originates from integrated DNA in hepatocyte . HBsAg production varies across genotypes with highest levels reported in genotype A individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There may be several explanations for our findings. HBsAg generation is reflective not only of cccDNA transcriptional activity, but also originates from integrated DNA in hepatocyte . HBsAg production varies across genotypes with highest levels reported in genotype A individuals.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports of differential sensitivity of qHBsAg detection across HBV genotypes. A study focusing on the ability to detect and measure HBsAg levels in the different genotypes showed that in genotype D the detection was 97% lower than genotype A and that genotype F had 30% lower detection than genotype A. Mutations at T143M of the surface gene in genotype A might reduce the ability to detect HBsAg by 44%, in contrast to the mutation T125M in genotype D patients which increased detection by 34% . A study in HBeAg‐negative chimpanzees demonstrated that >90% of liver mRNA originated from integrated DNA in contrast to less than 10% from cccDNA .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding was also verified in the subgenotype B2, C1, and C2 (Figure 3). It has long been known that different genotypes had marked differences in HBV natural history, disease progression, treatment response, and in vitro replication efficacy (22,23). In terms of genotype differences, the authors' previous study found that the core promoter transcriptional activity of genotype B was significantly higher than that of genotype C, hinting more production of pgRNA in genotype B (19).…”
mentioning
confidence: 99%
“…[17] Considering that there have been very few studies directly comparing the replication of different HBV genotypes this method could help evaluate some of the observed differences in natural history and disease progression.…”
Section: Discussionmentioning
confidence: 99%